Student nurses' views on shift patterns: What do they prefer and why? Results from a Tweetchat - Chiara Dall'Ora; Jessica Sainsbury; Chris Allen (Wiley, 2022)
Abstract Aim The main aim of the study was to understand student nurses' views around shift patterns. Design Qualitative study. Method We held a Tweetchat in May 2019, where we asked questions around the frequency of 12‐hr shifts working on placement; schedule flexibility while on placement; which shift patterns they preferred and why. Data from the Tweetchat were analysed using reflexive thematic analysis to generate themes from initial codes. Results Seventy‐three nursing students participated in the Tweetchat. The majority reported that they work 12‐hr shifts on placements, particularly when based in a hospital. We identified three themes: 'Achieving a personal equilibrium'; 'Meeting the needs of the care environment'; 'Factors affecting negotiation capacity'. Data highlighted a conflict for most students, where they preferred 12‐hr shifts because of more time off for study, paid work and leisure, while acknowledging 12‐hr shifts negatively affected their fatigue, exhaustion and led them to follow a poor diet and neglect exercise and sleep.